إمكانية تطبيق محاسبة استهلاك الموارد (RCA) في المنشآت الصناعية السورية (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This study aimed to identify the possibility of applying Resource Consumption Accounting(RCA) in the Syrian industrial environment, and to find out the availability of the necessary factors to apply it in entities, and define difficulties faces that application.the study included forty-nineindustrialentities in the provinces of Damascus and Damascus’scountryside,Data werecollectedthrough the distribution of questionnaire on the accounting departments within these entities.This study concluded thatthe productive structure in the Syrian industrial entitiescontaincharacteristics require adoption of modern cost accounting system as a (RCA) system,but there is great difficulty inapplying(RCA) because the lack of adoption factors in these entities, and there is obstacles towards that application.هدفت هذه الدراسة إلى تعرّف إمكانية تطبيق محاسبة استهلاك الموارد (RCA) في بيئة الصناعات السورية، ولمعرفة مدى توافر المقومات اللازمة لتطبيقها ضمن المنشآت،وتحديد المعوقات التي تواجها. شملت مجموعة الدراسة تسعا وأربعين منشأة صناعية في محافظتي دمشق وريفها، وتم جمع البيانات عبر توزيع استبانة على الأقسام المحاسبية ضمن هذه المنشآت.خلصت هذه الدراسة إلى احتواء البنية الإنتاجية في المنشآت الصناعية السورية على خصائص تتطلب تبني نظام محاسبة تكاليف حديث كنظام (RCA)، غير أن هناك صعوبة كبيرة في إمكانية تطبيقه نظراً لافتقار هذه المنشآت إلى مقومات تبنيه، ووجود معوقات تعترض تطبيقه.